RANCANG BANGUN APLIKASI PENILAIAN ESAI OTOMATIS MENGGUNAKAN ALGORITMA COSINE SIMILARITY STUDI KASUS MTS PERGURUAN MU’ALLIMAT - Agus Abdurrahman; Hadi Sucipto; Setyo Permadi, Ginanjar; Zein Vitadiar, Tanhella (Fakultas Teknologi Informasi, 2024)
This study aims to design and develop an automatic essay scoring application using the Cosine similarityalgorithm, with a case study at MTS Perguruan Mu’allimat. The main objectives of this research are tounderstand the process of creating an automatic answer correction system and to explore the application ofthe Cosine similarity method in the automatic essay answer correction system. The research begins withdesigning the system based on Object Oriented Programming (OOP) principles according to the systemrequirements analysis. The implementation of the Cosine similarity algorithm is conducted to calculate thesimilarity between students' answers and the correct answers. The results indicate that using the Cosinesimilarity algorithm in essay answer correction facilitates grading with reasonably good accuracy. Bytesting 10 student answers, the algorithm achieves an accuracy rate of 75.11% compared to manualcalculations. From these results, it can be concluded that this system is effective and accurate in scoringessay exams, and thus can be widely implemented to improve grading efficiency in educational settings.Keywords: essay grading application, Cosine similarity, automatic correction.